Critical information infrastructure security : 11th International Conference, CRITIS 2016, Paris, France, October 10-12, 2016, Revised selected papers /: 11th International Conference, CRITIS 2016, Paris, France, October 10-12, 2016, Revised selected papers. (2017) - Unknown
No abstract available